PERAN TUHA PUET GAMPONG DALAM MENGAWASI PEMBANGUNAN GAMPONG - Imran D, S.HI, M.H (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
The existence of the Tuha Peut institution in Blangkula Village, has not contributed maximally, this is based on observations and discussions by the author with the local community, that the implementation of the functions and tasks of the Tuha Peut has not been maximally carried out specifically in the supervision of the development of the Village, not as described in Qanun Number 5 of 2003 concerning Gampong governance and Regulation of the Governor of Aceh Number 25 of 2011 concerning General Guidelines for Implementing Gampong Government. The research method used was a qualitative study carried out by examining primary and secondary data and broader field data including reference material such as official documents issued by data collection carried out by conducting a literature review and document studies and interviews with respondents. The role of the Puja Gampong village in overseeing the construction of Blangkula Village must be in accordance with its duties and functions, related to the Blangkula Village Implementation Team (TPK), the Puah Puah must supervise optimally both in planning and at the time the activities take place and up to the reporting stage must be monitored. Furthermore, Tuha Puet also guarantees to the Gampong community that information disclosure to the community can be comprehensive and the development of the Gampong also runs smoothly and its evaluation, supervision also runs without problems.